Pengaruh Pemberian PGPR Bacillus SP. dan Pseudomonas SP. Asal Akar Bambu Apus terhadap Pertumbuhan Tanaman Jagung (Zea mays L.) - Hermalya Putri Hartono; Saiku Rokhim; Hanik Faizah (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
Corn is a substitute food crop for rice, and its number continues to increase yearly. Therefore, corn has experienced an increase in productivity because many Indonesian people like corn. The supporting factor for a plant to develop well is the provision of fertilizer. The fertilizers used by Indonesian farmers are generally not environmentally friendly and damage soil nutrients, such as inorganic fertilizers or chemical fertilizers. Therefore, environmentally friendly fertilizers from living organisms are needed to increase nutrients with biological fertilizers (PGPR). The aim of this research is (1)to determine the effect of PGPR Bacillus sp. and Pseudomonas sp. from the roots of apus bamboo on the growth of corn plants, (2) knowing the comparison of variations in the concentration of PGPR Bacillus sp. and Pseudomonas sp. on corn growth. This research was carried out from January to February 2024 at the laboratory and the greenhouse of BBPPTP Surabaya. The research sample used was 21 corn plant seeds. The research variables used were plant height, root length, number of leaves, root fresh weight, leaf fresh weight, root dry weight, and leaf fresh weight. The research results were analyzed using the SPSS test (One-way ANOVA and DMRT) and presented in a table. The result showed that isolates of Bacillus sp. and Pseudomonas sp. had a natural effect on corn, while the best concentration was given at a Bacillus sp. concentration of 15% and Pseudomonas sp. 15%.